Evaluation of a novel biofuel from unwanted waste and its impact on engine performance, emissions, and combustion characteristics in a diesel engine - Teoh, Y.H. (Royal Society of Chemistry, 2015)
The effect of a new biofuel source derived from waste palm oil mill effluent (POME) addition to diesel on engine performance, emissions, and combustion characteristics was investigated in a single-cylinder diesel engine under six different speed operations and at full load conditions. The experimental results suggested that there are some penalties in engine torque, brake power, brake specific fuel consumption (BSFC), and brake specific nitrogen oxide (BSNOx) with the presence of Biopro Diesel™ fuel in the blend. Moreover, there is an improvement in exhaust emissions with lower brake specific hydrocarbons (BSHC), brake specific carbon monoxide (BSCO) and smoke emissions by using Biopro Diesel™ fuel blends across all engine speeds. Besides, the tip surfaces of the injectors running with Biopro Diesel™ blends were found to be cleaner than that of an injector running with fossil diesel. Moreover, there is an improvement in the combustion process with a shorter total burning angle for Biopro Diesel™ fuel blends than that of diesel at all engine speeds. Overall, the results suggested that biofuel derived from waste POME blended with fossil diesel can be used satisfactorily in an unmodified diesel engine.